(untitled) (Journal of the College of Basic Education, 2022)
Gingivitis:is an inflammatory destructive disease mainly caused by microbial plaques. This study was aied isolate the pathogenic bacteria from gingival of 50 patients with oral gingivitis and 24 isolate by using. enriched and specific media used for isolation of bacteria. Identification of isolated bacteria performed by gram staining and biochemical tests. Twenty four isolate were gram negative and gram positive .The most frequent gram negative isolates were E coli 5(20.8%), Streptococcus spp 4(16.6%),Klebseilla spp 3(12.5%) ,Protus valgaris, Pseudomonas spp,Klebseilla oxytoca, Enterobacter cloacae,Escherichia alkalgance were 2(8.5%), and the last Protus mirabilis and Citrobacter spp were 1(4.1)% . Antibiotics bacterial resistant was most common in gram negative than in gram positive .The high bacterial antibiotics resistant was Ecoli Ampicillin, , Cephalexin, Ciprofloxacin and Ceftriaxone (100)% while the low bacterial resistant to antibiotics was Citrobacter spp . Bacterial gingivitis adhesion on epithelial cell and inhibition adhesion by sub MIC, used the plate test double dilution agar method for MIC & sub MIC ciprofloxacin antibiotic. The results of present study indicate that a wide range of pathogenic bacteria are responsible for destructions of gingival among patients. The diagnosis and treatment of the patients is necessary according to the public health care systems .The aim of study was isolate and identification the more pathogenic bacteria and the bacterial antibiotics resistant antibiotics and study inhibition adhesion virulence factor by sub MIC ciprofloxacin